Legal Regulation of the Status of Subjects of Special Competence in Relation to Public Administration in the Sphere of Intellectual Property in Ukraine - Leheza, Yevhen; Deliya, Yuriy; Ryzhkov, Eduard; Albul, Serhii; Shamara, Oleksandr (Jurnal Cita Hukum, 2021)
Relevant issues of the administrative and legal status of subjects of special competence in relation to public administration in the field of intellectual property are considered. Main  content. A circle of specified subjects in the system of subjects of public administration is determined. The role of subjects of special competence in the fulfilment of tasks of public administration in the sphere of intellectual property is identified. Classification of subjects of special competence regarding public administration in this field is presented. Features of the administrative or legal status of each group of subjects of special competence in relation to public administration in the field of intellectual property are analyzed. Specifics of the influence of these subjects on legal relations arising in the sphere of intellectual property are characterized. Materials and methods research based on the analysis of documentary sources. the  basis  is  the  dialectical  method  of  cognition  of  the  facts  of  social  reality,  on  which  the  formal legal and comparative legal approaches are largely based. Conclusions are drawn about the place of subjects of special competence in relation to public administration in the field of intellectual property among other subjects. Proposals on the necessity to improve current domestic legislation in the sphere of intellectual property are formulated.Keywords: Public administration; Intellectual property; Legal regulation; Relation; Sphere; Subjects of special competence Peraturan hukum status subjek kompetensi khusus dalam kaitannya dengan administrasi publik di bidang kekayaan intelektual di Ukraina  Abstrak.Masalah yang relevan dari status administrasi dan hukum mata pelajaran kompetensi khusus dalam kaitannya dengan administrasi publik di bidang kekayaan intelektual dipertimbangkan. Isi utama. Lingkaran mata pelajaran tertentu dalam sistem mata pelajaran administrasi publik ditentukan. Peran mata pelajaran kompetensi khusus dalam pemenuhan tugas administrasi publik di bidang kekayaan intelektual diidentifikasi. Klasifikasi mata pelajaran kompetensi khusus tentang administrasi publik di bidang ini disajikan. Fitur status administrasi atau hukum dari setiap kelompok mata pelajaran kompetensi khusus dalam kaitannya dengan administrasi publik di bidang kekayaan intelektual dianalisis. Spesifik pengaruh subjek ini pada hubungan hukum yang timbul di bidang kekayaan intelektual dicirikan. Bahan dan metode penelitian berdasarkan analisis sumber dokumenter. Basisnya adalah metode kognisi dialektis atas fakta-fakta realitas sosial, yang menjadi dasar sebagian besar pendekatan hukum formal dan hukum komparatif. Kesimpulan diambil tentang tempat mata pelajaran kompetensi khusus dalam kaitannya dengan administrasi publik di bidang kekayaan intelektual antara mata pelajaran lainnya. Proposal tentang perlunya meningkatkan undang-undang domestik saat ini di bidang kekayaan intelektual dirumuskan.Kata kunci: Administrasi publik, Kekayaan intelektual, Regulasi hukum, Hubungan, Lingkungan, Mata pelajaran kompetensi khusus Правовое регулирование статуса субъектов особой компетенции в отношении государственного управления в сфере интеллектуальной собственности в УкраинеАннотация Рассмотрены актуальные вопросы административно-правового статуса субъектов особой компетенции применительно к государственному управлению в сфере интеллектуальной собственности. Основное содержание. Определен круг указанных субъектов в системе субъектов государственного управления. Выявлена роль субъектов специальной компетенции в выполнении задач государственного управления в сфере интеллектуальной собственности. Представлена классификация предметов особой компетенции государственного управления в этой области. Анализируются особенности административно-правового статуса каждой группы субъектов особой компетенции применительно к государственному управлению в сфере интеллектуальной собственности. Охарактеризована специфика влияния этих субъектов на правоотношения, возникающие в сфере интеллектуальной собственности. Материалы и методы исследования на основе анализа документальных источников. в основе лежит диалектический метод познания фактов социальной действительности, на котором в значительной степени базируются формально-правовой и сравнительно-правовой подходы. Сделаны выводы о месте субъектов особой компетенции по отношению к государственному управлению в сфере интеллектуальной собственности среди других субъектов. Сформулированы предложения о необходимости совершенствования действующего украинского законодательства в области интеллектуальной собственности.Ключевые слова: Государственное управление, Интеллектуальная собственность, Правовое регулирование, Отношения, Сфера, Субъекты особой компетенции.